The inflation-targeting debate - Bernanke, Ben; Woodford, Michael, 1955- (Studies in income and wealth., 2004)
Over the past fifteen years, a significant number of industrialized and middle-income countries have adopted inflation targeting as a framework for monetary policymaking. As the name suggests, in such inflation-targeting regimes, the central bank is responsible for achieving a publicly announced target for the inflation rate. While the objective of controlling inflation enjoys wide support among both academic experts and policymakers, and while the countries that have followed this model have generally experienced good macroeconomic outcomes, many important questions about inflation targeting.